ANALYSIS OF LIFESTYLE, PRICE DISCOUNT AND PRODUCT QUALITY ON IMPULSIVE BUYING IN ISSUE CLOTHING STORE - Bunyamin Bunyamin; Manda HM; Andi Hadidu (Sekolah Tinggi Pariwisata Mataram, 2021)
Frequently consumers make purchases without deliberation even though the goods that have been bought are not necessarily used, this action is called impulsive buying. This study aims to analyse the influence of Lifestyle, Price Discounts, and Product Quality on Impulsive Purchases. The method used is quantitative. The sampling technique is using the Non-Probability Sampling method with the Accidental Sampling technique. The sample used was 147 consumers at the Issue clothing store in Makassar City. Data analysis used multiple linear regression with data processing using SPSS version 21. The results showed that lifestyle, price discounts, and product quality partially and simultaneously had a positive and significant effect on impulsive buying.